Kiat sukses menjadi pendidik berjiwa Entrepreneur - Andinny, Yuan; Lestari, Indah; Ramdani, Irham (PT. Lancar Media Komunikasi, 2022)
Every teacher must have an entrepreneurial instinct as a source of student learning. That is, to produce teachers and students who have entrepreneurial instincts from an early age, teachers must be examplesof how to have entrepreneurial instincts. So to be a successful entrepreneur, the main requirement that must be possessed is to have an entrepreneurial spirit and character. The entrepreneurial spirit andcharacter are influenced by skills, abilities or competencies. Competence itself is determined by knowledge and business experience. An entrepreneur requires several skills namely, basic skills and special skills. In order to become a qualified teacher, the teacher must have an entrepreneurial spirit. TEACHER PRENEUR SHIP will be able to bring up the mental attitude and spirit of a teacher who is always active or creative, empowered, creative, passionate, and humble in trying to improve the quality of education through his business activities at school. A teacher who has the nature of TEACHER PRENEUR SHIP will be able to create a new teacher who does not like to question problems, but prefers to solve a problem. A teacher who has an entrepreneurial spirit has 3 competencies, the first is Teaching Skills, Conceptual Skills, and Human Skills.